Formulation of Hand Cream Essential Oil of Basil (Ocimum basilicum) Leaves - Yenni Puspita Tanjung; Tubagus Akmal; Haifa Virginia (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
Basil (Ocimum basilicum) leaf essential oil contains terpenoid compounds that have antibacterialactivity. This study aims to obtain hand cream preparations of basil essential oil, as well as to determinethe effect of concentration variation of liquid paraffin on the results of the evaluation of the preparation.In this study, three formulations of hand cream preparations of basil essential oil were made withthree variations in the concentration of liquid paraffin, namely F1 (9%), F2 (10%), and F3 (11%).Furthermore, the preparation was evaluated for 28 days at room temperature (15-300C) and humidity(60-80%) which included organoleptic, pH, viscosity, homogeneity, spreadability, and type of emulsion.The results showed that formulas F1, F2, and F3 met all the requirements of organoleptic, pH, viscosity,homogeneity, spreadability, and type of emulsion. The results of the statistical analysis showed thatvariations in liquid paraffin concentrations had a significant effect (p<0.05) on the evaluation ofviscosity and did not significantly affect the evaluation of organoleptic, evaluation of pH, evaluation ofhomogeneity, evaluation of spreadability, and evaluation of emulsion type.